Learning Style and Learning Achievement of Students of FKIP Universitas Riau In Learning English - Hadriana, Hadriana; Primahardani, Indra; Mahdum, Mahdum (Journal of Educational Sciences, 2019)
Becoming a successful student is a dream of every student and parents. Learning style is one of things that might influence that success. This research intended to find out if there is a correlation between learning styles and learning achievement of students of FKIP Universitas Riau in learning English. 300 students were involved as the sample of the research. The research was conducted during the even semester academic year 2018-2019 and the research data was collected in June 2019. The instruments of the research were adapted from Vark Questionnaire Version8.01 and students’ grades in their English class.Percentage and mean used to represent the frequency ofdata for descriptive analysis and inferential analysis was carried out. Since the data of students’ learning style and learning achievement obtained were not normally distributed, associative Kendall’s Tau-c correlation formula was used to find out the relationship between learning style and learning achievement. Based on the data analysis, it can be concluded that there is a relationship between the students learning style and their learning achievement.